Speeches delivered by Colonel Loyd-Lindsay, ... to the Newbury Conservative Working Men's association, January 29th, 1880 (National Union of Conservative and Constitutional Associations, 1880)
Also titled : The foreign policy of the government, especially with reference to eastern affairs. - Pamphlet volume.